Design Approach of Biologically-Inspired Musculoskeletal Humanoids. (29th April 2013) - Nakanishi, Yuto; Ohta, Shigeki; Shirai, Takuma; Asano, Yuki; Kozuki, Toyotaka; Kakehashi, Yuriko; Mizoguchi, Hironori; Kurotobi, Tomoko; Motegi, Yotaro; Sasabuchi, Kazuhiro; Urata, Junichi; Okada, Kei; et al.
In order to realize more natural and various motions like humans, humanlike musculoskeletal tendon-driven humanoids have been studied. Especially, it is very challenging to design musculoskeletal body structure which consists of complicated bones, redundant powerful and flexible muscles, and large number of distributed sensors. In addition, it is very challenging to reveal humanlike intelligence to manage these complicated musculoskeletal body structure. This paper sums up life-sized musculoskeletal humanoids Kenta, Kotaro, Kenzoh and Kenshiro which we have developed so far, and describes key technologies to develop and control these robots.